Hubungan Kelimpahan Zooplankton Terhadap Hasil Tangkapan Alat Tangkap Togok Di Kelurahan Kampung Nelayan Tanjung Jabung Barat Provinsi Jambi - Prabowo, Tri; Asra, Revis; Amelia, Jasmine Masyitha (Universitas Jambi, 2019)
This study aimed to determine the parameters of aquatic environments based on physical-chemical factors, zooplankton diversity, and zooplankton abundance relationships on togok catch results. The sampling is done 3 times with 1 week interval. Based on the value of DO note that station 1 is categorized as moderate polluted, while stations 2 and 3 are still in the low polluted category. During the study there were 8 types of zooplankton consisting of Brachionusdimidiatus, Brachionus quadratus, Calanus gracilis, Calanus minor, Euterpina acutifrons, Oikopleura laboradoriensis, Oithona attenuate, and Nauplius. An index value of zooplankton averages of 1.12-1.44 indicates that moderate diversity with moderate distribution of individuals and levels of contaminated pollution is moderate. The zooplankton dominance index value shows that there is no dominant type with value 0,29-0,34. Pearson correlation results show there is no relationship between zooplankton abundance of togok catches, with a value of 0.882.